2021
DOI: 10.2217/nnm-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Biocompatibility and Degradability of Carbon Nanoparticles for Photothermal Therapy of Lung Cancer

Abstract: Aim: To investigate near infrared-induced phototoxicity toward lung cancer cells, and the biodegradability and effect on immune cells of glucose-derived carbon nanoparticles (CNPs). Methods: The human A549 lung adenocarcinoma cell line was used as a model to study the phototoxicity of CNPs. The biodegradability and the effect on immune cells was demonstrated in primary human neutrophils and macrophages. Results: Near infrared-activated CNPs elicited rapid cell death, characterized by the elevation of heat shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In fact, they exhibit no cytotoxicity against the cells of the immune system and are hemocompatible . Finally, previous data suggest that CNPs are not biopersistent due to degradation by neutrophils …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In fact, they exhibit no cytotoxicity against the cells of the immune system and are hemocompatible . Finally, previous data suggest that CNPs are not biopersistent due to degradation by neutrophils …”
Section: Introductionmentioning
confidence: 94%
“… 15 Finally, previous data suggest that CNPs are not biopersistent due to degradation by neutrophils. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…114 In addition, previous data suggest that HCNPs are slowly degraded by neutrophils. 56 Finally, depending upon the bulk structure, some of these materials exhibit physical properties like fluorescence, PT and PD capabilities suggest a possible use as both therapeutic and diagnostic agents themselves. 111 Previous studies by some of us found that, when irradiated with an NIR laser beam (945 nm, 1.3 W/cm 2 ), HCNPs efficiently generate heat 112 (Figure 5).…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…58 On the other hand, the carbon shell prevent the rapid release of iron ions in the intracellular compartments that may induce oxidative stress. 62 Carbon nanomaterials are known to be degraded by myeloperoxidase, 65,66 the enzyme expressed mainly in neutrophils, which generates the strong oxidant hypochlorous acid, and by hydrogen peroxide in macrophages. 67,68 To investigate the possible degradation of the carbon shell by these oxidants, the sample has been incubated in NaClO or H 2 O 2 at two different concentrations (0.2 and 2 mM).…”
Section: Surface Reactivitymentioning
confidence: 99%